Analisis Semiotika Pierce terhadap Pasangan Prabowo-Gibran dalam Pilpres 2024 - Sjoraida, Diah Fatma; Sudi, Mohamad; Meliala, Robbikal Muntaha; Mayasari, Silvina; Palupi, Rety (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
In the 2024 presidential election, campaign signs play a crucial role in political communication, shaping public perceptions of candidate pairs. However, there has been limited research examining the influence of these signs through Peirce's semiotic framework. This study aims to analyze the effect of the Prabowo-Gibran campaign signs during the 2024 presidential election using Peirce's semiotic approach. Additionally, it seeks to explore the broader implications of these findings for political communication strategies in elections. Peirce's semiotic theory is applied as an analytical tool to interpret the meaning conveyed by the Prabowo-Gibran campaign signs. Data were gathered through observations of the campaign signs and analyzed using semiotic interpretation, focusing on representations, objects, and interpretants. The influence of these signs on public perception and voter support was then assessed. The findings reveal that the Prabowo-Gibran campaign signs effectively conveyed messages of courage, collaboration, and public health. These signs were positively received by the public, shaping the image of the pair as strong leaders capable of fostering cooperation. The results are crucial for understanding political communication strategies, as recognizing the meaning and impact of campaign signs can help inform more effective strategies to shape voter attitudes. Based on Peirce’s semiotic analysis, it is concluded that the Prabowo-Gibran campaign signs have a significant effect on public perception and voter support
Keywords: 2024 Presidential Election; Peirce’s Semiotics; Prabowo-Gibran